A model of recurrent concussion that leads to long-term motor deficits, CTE-like tauopathy and exacerbation of an ALS phenotype. Issue 6 (December 2016) - Thomsen, Gretchen M.; Ma, Annie M.; Ko, Ara; Harada, Megan Y.; Wyss, Livia; Haro, Patricia S.; Vit, Jean-Philippe; Shelest, Oksana; Rhee, Peter; Svendsen, Clive N.; Ley, Eric J.
Abstract : BACKGROUND: Concussion injury is the most common form of traumatic brain injury (TBI). How recurrent concussions alter long-term outcomes is poorly understood, especially as related to the development of neurodegenerative disease. We evaluated the functional and pathological consequences of repeated TBI over time in wild type (WT) rats as well as rats harboring the human SOD1 G93A mutation ("SOD1"), a model of familial amyotrophic lateral sclerosis (ALS). METHODS: A total of 42 rats, 26 WT and 16 SOD1, were examined over a study period of 25 weeks (or endpoint). At postnatal day 60, 20 WT and 7 SOD1 rats were exposed to mild, bilateral TBI once per week for either 2 weeks (2×TBI) or 5 weeks (5×TBI) using a controlled cortical impact device. Six WT and nine SOD1 rats underwent sham injury with anesthesia alone. Twenty WT rats were euthanized at 12 weeks after first injury and six WT rats were euthanized at 25 weeks after first injury. SOD1 rats were euthanized when they reached ALS disease endpoint. Weekly body weights and behavioral assessments were performed. Tauopathy in brain tissue was analyzed using immunohistochemistry. RESULTS: 2XTBI injured rats initially demonstrated recovery of motor function but failed to recover to baseline within the 12-week study period. Relative to both 2XTBI and sham controls, 5XTBI rats demonstrated significant deficits that persisted over the 12-week period. SOD1 5XTBI rats reached a peak body weight earlier than sham SOD1 rats, indicating earlier onset of the ALS phenotype. Histologic examination of brain tissue revealed that, in contrast with sham controls, SOD1 and WT TBI rats demonstrated cortical and corpus collosum thinning and tauopathy, which increased over time. CONCLUSIONS: Unlike previous models of repeat brain injury, which demonstrate only transient deficits in motor function, our concussion model of repeat, mild, bilateral TBI induced long-lasting deficits in motor function, decreased cortical thickness, shrinkage of the corpus callosum, increased brain tauopathy, and earlier onset of ALS symptoms in SOD1 rats. This model may allow for a greater understanding of the complex relationship between TBI and neurodegenerative diseases and provides a potential method for testing novel therapeutic strategies.